Jesus and the remains of his day: studies in Jesus and the evidence of material culture - Evans, Craig A. (endrickson Publishers Marketing, 2015)
A tale of two cities: what we have learned from Bethsaida and Magdala -- A boat, a house, and an ossuary: what can we learn from the artifacts? -- Excavating Caiaphas, Pilate, and Simon of Cyrene: assessing the literary and archaeological evidence -- Have you never read?: Jesus and literacy -- Shout at the devil: Jesus and Psalm 91 in the light of early Jewish interpretation -- Hang him on a tree until dead: hanging and crucifixion in second temple Israel -- The family buried together stays together: on the burial of the executed in family tombs -- Death becomes him: on the execution and burial of Jesus -- Keeping up appearances: the Talpiot tomb façade in context -- The talking dead: postmortem beliefs in pagan, Jewish, and Christian epitaph